Exploring the synergy of enzymes, nutrients, and gene networks in rice starch granule biogenesis - Warwate, Sunil Indrajit; Awana, Monika; Thakare, Swapnil S.; Krishnan, Veda; Kumar, Suresh; Bollinedi, Haritha; Arora, Ajay; Sevanthi, Amitha Mithra; Ray, Mrinmoy; Praveen, Shelly; Singh, Archana (Frontiers in Nutrition, 2024)
A total 200 rice genotypes were analyzed for total starch content (TSC), amylopectin content (APC), and amylose content (AC). The clustering of these rice genotypes was done based on their AC. Further, these genotypes were categorized into three groups up to 10% amylose-low, 10-26% amylose-medium, and more than 26% amylose-high. Among them, six genotypes 1 from low AC (NJ-72), 2 from medium AC (UPRI-2003-18, PRR-126), and 3 from high AC (RNRM-7, Urvashi and Ananga) were selected. The genotypes selected from the NJ-72 showing low RS and Ananga with high RS were selected for investigation of enzymatic activities of starch biosynthesis, metabolites accumulation, and expressions of 20 starch biogenesis genes in developing endosperm. Starch branching enzymes (SBE) and starch synthase (SS) activities peaked at 13 days after anthesis (DAA), while starch debranching enzymes (DBE) were most active at 18 DAA. In Ananga, TSC, AC, APC, and RS levels progressively increased from 3 to 23 DAA. Ananga showed 1.25-fold upregulation of granule-bound starch synthase I (GBSSI) at 18DAA. Higher expressions of SSI and SBEIIb were observed in NJ-72 at 13DAA. PUL2 was predominantly expressed followed by ISA1. GBSSI was positively correlated with both AC and RS while SS, SBE, and DBE were positively related to APC. This research could lead to the development of rice varieties with improved nutritional qualities, such as higher RS content, which is beneficial for human health due to its role in lowering glycemic response and promoting gut health. Additionally, the study provides insights into how the modulation of key genes and enzymes can affect starch composition, offering strategies to breed rice varieties tailored for specific dietary needs or industrial applications.